MORAL VALUES OF THE CHARACTERS AND CHARACTERS ANALYSIS IN THE NOVEL ‘READY PLAYER ONE’ BY ERNEST CLINE - Henny Belgrita Ginting (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: The purpose of the research is to demonstrate the moral values and characters in the novel “Ready Player One” by Ernest Cline. This research is designed as qualitative research. The approach that the writer used is the qualitative approach. The data are collected by analyzing the data found in the novel. The analysis of the novel is observed in the text and dialogues. The results of the research are in the form of moral values and characters analysis. 1) The moral values in the novel are: Justice is 34,62%, honesty is 26,92%, responsibility is 23,08%, and beneficence is 15,38%. 2) The characters which emerge in the novel “Ready Player One” Protagonist are 55,86%, Foil is 37,93%, and the antagonist is 6,21%. Moral values that dominate, or the novel would like to convey particularly to the readers, are Justice and Honesty. It means that the character who dominates the film is the protagonist.Keywords: moral; value; moral value; character; novel